Acyclovir versus Valganciclovir for Preventing Cytomegalovirus Infection in Intermediate-Risk Liver Transplant Recipients. (March 2015) - McKeen, Jaclyn T.; Tsapepas, Demetra S.; Li, Hanlin; Anamisis, Anastasia; Martin, Spencer T.
Context: Cytomegalovirus (CMV) is an opportunistic infection that causes profound morbidity and mortality after orthotopic liver transplant (OLT). The CMV immunoglobulin G serostatuses of donors and recipients are the main factors influencing risk for development of CMV infection after transplant. Objective: To compare acyclovir and valganciclovir for preventing CMV infection after OLT. Design, Setting, and Patients: Retrospective assessment of adult OLT recipients at intermediate risk for CMV infection at New York Presbyterian Hospital. Intervention: All patients received ganciclovir 5 mg/kg intravenously every 12 hours or valganciclovir 900 mg orally every 12 hours for 7 days after transplant. On postoperative day 8, patients received antiviral prophylaxis according to risk stratification: acyclovir 800 mg orally 3 times daily in donor seronegative/recipient seropositive (D-/R+) patients or valganciclovir 900 mg orally once daily in donor seropositive/recipient seropositive (D+/R+) patients. Main Outcome Measure: Composite incidence of CMV infection, syndrome, or tissue-invasive disease. Results: Of 275 OLT recipients, 89 were at intermediate risk for CMV infection (29 D−/R+, 60 D+/R+). CMV infection, syndrome, or tissue-invasive disease occurred in 1 patient (3%) in the D−/R+ group and 5 patients (8%) in the D+/R+ group ( P =.66). One patient (3%) in the D−/R+ group had a CMV infection develop. Five D+/R+ recipients (8%) had CMV infection; 3 of them had CMV syndrome (5%), 1 had CMV hepatitis (1.6%), and the other had CMV esophagitis (1.6%); all events occurred after prophylaxis was discontinued. The rates of CMV infection were similar in D−/R+ patients treated with acyclovir and D+/R+ patients receiving valganciclovir. This risk-stratified approach to viral prophylaxis after OLT resulted in an acceptable rate of CMV infection in D−/R+ recipients and may avoid the costs and adverse effects associated with valganciclovir therapy.